1977
DOI: 10.1159/000114877
|View full text |Cite
|
Sign up to set email alerts
|

Karyometric Changes in Human Muscle with Age

Abstract: Human muscle cell growth was studied to investigate the nucleo-cytoplasmic ratio during development and ageing. The mean muscle fibre size, as well as the number and size of myonuclei were estimated in human muscle biopsies from normal individuals whose ages ranged from 1 to 71 years. Changes in muscle fibre size were accompanied by similar changes in nuclear number, the size of which remained the same. This resulted in a constant nucleo-cytoplasmic ratio during the age range studied. The role of the satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 0 publications
2
16
2
Order By: Relevance
“…The only other study on human myonuclear domain size development that we are aware of reported that the nucleo-cytoplasmic ratio remained constant between 1 and 2.5 years to 12 and 30 years (Vassilopoulos et al, 1977). At first glance this appears at odds with our data, but it should be noted that they used fiber diameter as a measure of fiber size.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The only other study on human myonuclear domain size development that we are aware of reported that the nucleo-cytoplasmic ratio remained constant between 1 and 2.5 years to 12 and 30 years (Vassilopoulos et al, 1977). At first glance this appears at odds with our data, but it should be noted that they used fiber diameter as a measure of fiber size.…”
Section: Discussioncontrasting
confidence: 87%
“…In rodents it increases its size 4-fold between 4 days and 3 months after birth (Kelly, 1978;Kawano et al, 2008;White et al, 2010). Though in humans the myonuclear domain has also been found to increase 2.5-fold from toddler to adolescent (Vassilopoulos et al, 1977), a detailed time course of this increase is yet lacking, especially during infancy.…”
mentioning
confidence: 99%
“…Two previous human studies suggested that myonuclei are not lost during normal aging regardless of whether fiber size is altered. Vassilopoulos et al40 obtained muscle biopsies from normal individuals whose ages ranged from 1 to 71 years and reported that changes in muscle fiber size were accompanied by similar changes in nuclear number, which resulted in a constant nucleocytoplasmic ratio in the age range studied. Manta et al22 performed an autopsy study of 15 individuals whose ages ranged from 17 to 82 years and found that the nucleocytoplasmic ratio increased significantly after the age of 60 years, due to a decrease in mean fiber size, whereas the number and the size of myonuclei remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between the number of myonuclei and fibre size has been reported in trained young (Kadi et al, 1999) and old (Manta et al, 1987;Hikida et al, 2000) individuals, but not in untrained elderly subjects (Hikida et al, 1998), reflecting an aging-and ⁄ or atrophy-related deterioration of this relationship (Ohira et al, 1999). In humans, there are a few reports in the literature on the effects of aging on myonuclear density, describing a constant (Vassilopoulos et al, 1977) or decreased (Manta et al, 1987) cytoplasmic density in old age. In addition, an increased myonuclear density has been observed in elderly men and women, but the study did not correct for muscle fibre size (Kadi et al, 2004a,b).…”
Section: Introductionmentioning
confidence: 99%